Heuristic or analytical pathway? A multimodal analysis of communicative features in Southern Italian Renewable Energy Communities (RECs) - D’Errico, Francesca; Sportelli, Carmela; De Simone, Evelyn; Procentese, Fortuna; Scardigno, Rosa (Frontiers in Communication, 2025)
IntroductionRenewable Energy Communities (RECs) represent a multifaceted phenomenon at the intersection of technical, social, and economic dimensions. Despite their potential to foster sustainable transitions, RECs remain relatively unfamiliar and abstract to the broader public.MethodsThis study addresses this gap by examining how persuasive communication strategies are employed in public informative videos aimed at raising awareness and encouraging citizen participation in REC projects. Drawing on the Elaboration Likelihood Model (ELM), we investigate the extent to which analytical versus heuristic pathways are activated in media discourse on RECs. We conducted an in-depth qualitative multimodal analysis of four videos (approximately 20 minutes in total), each representing a different type of REC (solidarity-based vs. non-solidarity-based; under development vs. fully implemented) located in Southern Italy. The integrated method combined observational analysis of speech and audiovisual features, enabling a systematic exploration of verbal, paraverbal, and visual components.ResultsThe analysis identified three distinct communicative strategies: (1) an analytical approach, privileging factual data, bureaucratic language, and appeals to institutional authority (Sant’Arsenio); (2) an emotional approach, centered on regional identity and collective pride (Roseto); and (3) a balanced approach, blending analytic and affective cues (Naples and San Severo). These strategies varied according to REC type and project stage, with implemented and solidarity-based projects more frequently integrating emotional and community-oriented framings.DiscussionFindings highlight how message framing, the balance of analytic versus heuristic cues, and audiovisual choices can significantly influence public representations of RECs. Tailored communication strategies, sensitive to both project type and audience characteristics, appear crucial for fostering engagement, legitimacy, and collective identification with RECs. Implications are discussed in terms of public policy design, sustainability education, and environmental advocacy, underscoring the role of communication as a lever for promoting active energy citizenship.